Development of the largest residential district of Lviv – Sykhiv - Cherkes, Bohdan (Видавництво Львівської політехніки, 2015)
The article describes the peculiarities of formation of the largest socialistic residential district, Sykhiv of Lviv. The text reviews the transformational processes that had been taking place in Sykhiv during the contextual shifts of the last few decades. Описано особливості формування соціалістичного району масової житлової забудови “Сихів” у Львові. Розглянуто трансформаційні процеси, які відбулись у районі в умовах зміни контекстів.
Розвиток найбільшого житлового району Львова – Сихова
Keywords: large panel housing estate; residential district; micro district; urban transformation; район масової житлової забудови; житловий район; мікрорайон; міська трансформація